New-onset organ dysfunction as a screening tool for the identification of sepsis and outcome prediction in dogs with systemic inflammation - Ciuffoli, Elena; Troìa, Roberta; Bulgarelli, Cecilia; Pontiero, Alessandra; Buzzurra, Francesca; Giunti, Massimo (Frontiers in Veterinary Science, 2024)
Introduction: Sepsis in people is defined as a life-threatening organ dysfunction (OD) caused by a dysregulated host response to infection. In veterinary medicine, sepsis is still defined by the presence of systemic inflammation plus the evidence of infection. Based on recent veterinary studies, multiorgan dysfunction syndrome (MODS) has been associated with a worse outcome in sepsis. Thus, the screening for OD is warranted to identify the most critically ill patients. The aim of this study was to investigate the diagnostic value of new-onset OD for the prediction of sepsis and outcome in a population of critically ill dogs with systemic inflammation.Material and methods: Dogs admitted to the Emergency Room and/or the Intensive Care Unit with systemic inflammation, defined by a serum C-reactive Protein concentration > 1.6 mg/dL, were retrospectively included. Enrolled dogs were categorized according to the presence of sepsis or noninfectious systemic inflammation. The presence of newly diagnosed OD was assessed based on criteria adapted from human literature and previously reported canine criteria.Results: 275 dogs were included: 128 had sepsis and 147 had non-infectious systemic inflammation.The frequency of new-onset OD was not different between these groups. Only the presence of fluid-refractory hypotension was significantly associated with a diagnosis of sepsis (OR 10.51, P<0.0001). The frequency of at least two ODs was significantly higher in non-survivors compared to survivors, according to both the human and the veterinary criteria considered for the study (P=0.0001 and P=0.0004, respectively). Specifically, the presence of acute kidney injury, stupor or coma, prolonged Prothrombin Time and decreased Base Excess were associated with a higher risk of death in the multivariate binary logistic regression. Discussion: In this population of critically ill dogs with systemic inflammation, the detection of newly diagnosed ODs was not able to predict sepsis diagnosis, other than the presence of fluidrefractory hypotension. However, given the strong prognostic significance associated with ODs, our results support the early screening for ODs in any severe inflammatory critical care condition to identify high-risk patients and optimize their management.